Case-Control Study on Factors Associated with Hyperglycemic Crises in Diabetic Adults Attended in the Emergency Unit of a General Hospital in Lima: Estudio de casos y controles sobre factores asociados a crisis hiperglucémicas en adultos diabéticos atendidos en la unidad de emergencia de un Hospital General de Lima - Lopez Bautista, Madeleine (2024)
Introduction: Diabetes mellitus represents a significant public health challenge; hyperglycemic crises are serious complications that can result in morbidity or death.Objective: To establish factors associated with hyperglycemic crises (HC) in diabetic adults attended in a hospital in Lima.Methods: An observational, retrospective, and analytical case-control study was conducted in a General Hospital in Lima between 2015 and 2019. A total of 186 medical records (62 cases and 124 controls) were selected through simple random sampling. The outcome was HC, defined as diabetic ketoacidosis, hyperosmolar hyperglycemic state, and mixed state. The variables included age, sex, area of residence, health insurance, duration of disease, comorbidities, acute infections, and medication adherence. Data were analyzed using Chi-Square tests and Fisher's exact test, calculating crude (cOR) and adjusted (aOR) Odds Ratios.Results: In the bivariate analysis, factors associated with HC were sex (p=0.029), age (p<0.001), duration of disease (p=0.001), and medication adherence (p<0.001). No relationship was found with variables such as residence, health insurance, acute infectious processes, and comorbidities (p>0.05). In the multivariate analysis, factors associated with HC were age (aOR: 2.85; 95% CI: 1.41–5.79; p=0.004) and non-adherence to medication (aOR: 3.87; 95% CI: 1.84–8.18; p<0.001).Conclusion: Factors associated with HC are age and non-adherence to medication.